Neonatal sepsis in dogs: Incidence, clinical aspects and mortality - Nobre Pacifico Pereira, Keylla Helena [UNESP]; Fuchs, Kárita da Mata [UNESP]; Hibaru, Viviane Yukari [UNESP]; Cruz dos Santos Correia, Luiz Eduardo [UNESP]; Ferreira, João Carlos Pinheiro [UNESP]; Ferreira de Souza, Fabiana [UNESP]; Machado, Luiz Henrique de Araújo [UNESP]; Chiacchio, Simone Biagio [UNESP]; Gomes Lourenço, Maria Lucia [UNESP] (Elsevier, 2022)
The neonatal period in dogs remains associated with high mortality rates. Sepsis is the main cause of neonatal losses during the first three weeks of life. Additionally, failure in the clinical assessment and early diagnosis of sick newborns is still common, leading to inadequate care, which contributes to a high mortality rate. Thus, the objective of this study was to describe the incidence of sepsis in canine newborns, the clinical aspects involved, the main isolated bacterial agents and mortality rates to facilitate clinicians’ early recognition of this condition. Of the 152 litters and 762 neonates evaluated, 14.8% (113/762) had sepsis or septic shock, and the mortality rate among affected puppies was 25.6% (29/113). Among the puppies with sepsis that died, early mortality (0–2 days of age) occurred in 69% (20/29) of affected neonates, and late mortality (3–30 days of age) occurred in 31% (9/29) of affected neonates. Significant differences (p < 0.0001) in clinical parameters (heart and respiratory rates, blood glucose, body temperature, peripheral oxygen saturation and reflexes) were noted among healthy neonates and neonates with sepsis and septic shock. The main and most relevant clinical signs were apathy, a reduced sucking reflex, diarrhea, the neonatal triad, failure to gain weight, bradycardia, dyspnea, cyanotic mucous membranes, body erythema, reduced peripheral oxygen saturation, cyanosis and tissue necrosis in the extremities. The mother may have been the main source of infection for 87.6% (99/113) of neonates with sepsis. Most infections were transmitted during pregnancy (68%, 77/113) in cases of neonatal sepsis. The major source of infection for neonates was the uterus, followed by breast milk and maternal oropharyngeal secretions. The most frequently isolated bacterial agent was Escherichia coli, accounting for 25.6% (29/113) of sepsis cases. The morbidity and mortality of neonatal sepsis in dogs is high. The clinical evaluation and diagnosis of sepsis in neonates differ from those in adult animals. Thus, knowledge of the neonatal particularities of sepsis is essential for proper clinical management and greater survival of these patients.
Keywords: Bacterial infection; Neonate; Newborn dog; Puppy; Septic shock